Konsep Skematik Desain Pada Revitalisasi Museum Subak Di Kabupaten Tabanan, Provinsi Bali: Bahasa Indonesia - I Kadek Rama Adhi Aryana; I Kadek Merta Wijaya; I Nengah Sinarta (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The Subak Museum which was created to maintain and strengthen Subak is not assessed at a level consistent with the appreciation experienced by Subak in 2012. The Subak Museum opened 40 years ago, but due to several circumstances, tourist visit data for the last six years fluctuated but tended to fall, therefore it is necessary to have a movement to restore visitor interest in visiting the Subak Museum by revitalizing it. In the Revitalization of the Tabanan Subak Museum, it is hoped that it can become a means of education and other supporting facilities such as research, protection and also recreation because the Subak Museum currently only facilitates exhibition halls. rice fields, along with the development of technology and the times.